HAK DAN KEWAJIBAN ASASI MANUSIA DALAM PERSPEKTIF ISLAM - Ahmad Mukri Aji (SALAM: Jurnal Sosial dan Budaya Syar-i, 2015)
Human rights in Islam are not foreign goods, because the discourse on human rights in Islam is earlier when compared to other concepts or teachings. In other words, Islam came inherently carrying teachings about human rights. Islamic teachings on human rights can be found in the main source of Islamic teachings, namely the Koran and Hadith which are the source of normative teachings, also found in the practice of Muslim life. Apart from Human Rights (HAM), there are Human Obligations (KAM) which act as a balance and harmonization in order to achieve the benefit of the ummah.Keywords: Islamic law, human rights, KAM AbstrakHAM dalam Islam sebenarnya bukan barang asing, karena wacana tentang HAM dalam Islam lebih awal jika dibandingkan dengan konsep atau ajaran lainnya. Dengan kata lain, Islam datang secara inheren membawa ajaran tentang HAM. Ajaran Islam tentang HAM dapat dijumpai dalam sumber utama ajaran Islam yaitu al-Qur`an dan Hadis yang merupakan sumber ajaran normatif, juga terdapat dalam praktik kehidupan umat Islam. Selain Hak Asasi Manusia (HAM) ada Kewajiban Asasi Manusia (KAM) yang menjadi penyeimbang dan penyelaras guna mencapai kemaslahatan umat. Kata kunci: Hukum Islam, HAM, KAM